Pembuatan Gedung Serba Guna di Universitas Bangka Belitung - Anila Ismi; Elviera Wilda Yanti; Alfan Mubarak; Sultan Sultan; M. Afdal S (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Universitas Bangka Belitung (UBB) is committed to improving the quality of facilities and infrastructure to support various academic and non-academic activities. This article discusses the feasibility of constructing a Multipurpose Building (GSG) designed to be a multifunctional activity center. This study uses a financial analysis method with parameters of Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Payback Period (PP). The results of the analysis show that this project is feasible to be implemented with an NPV value of Rp1,059,940,033 (10% interest rate) and an IRR of 13.66%. The construction of this building is expected to have a positive impact on the academic community and the surrounding community.